2012
DOI: 10.1371/journal.pone.0053214
|View full text |Cite
|
Sign up to set email alerts
|

SOLiD-SAGE of Endophyte-Infected Red Fescue Reveals Numerous Effects on Host Transcriptome and an Abundance of Highly Expressed Fungal Secreted Proteins

Abstract: One of the most important plant-fungal symbiotic relationships is that of cool season grasses with endophytic fungi of the genera Epichloë and Neotyphodium. These associations often confer benefits, such as resistance to herbivores and improved drought tolerance, to the hosts. One benefit that appears to be unique to fine fescue grasses is disease resistance. As a first step towards understanding the basis of the endophyte-mediated disease resistance in Festuca rubra we carried out a SOLiD-SAGE quantitative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 114 publications
(148 reference statements)
13
82
2
Order By: Relevance
“…In order to fully understand the impact of Epichloë infection on perennial ryegrass gene expression, we performed deep mRNA sequencing (RNAseq) on endophyte‐infected and endophyte‐free plants. This study furthers an earlier SOLiD‐SAGE analysis of E. festucae in association with red fescue grass performed by Ambrose & Belanger () that identified c . 200 host genes which are differentially expressed during a mutualistic association.…”
Section: Introductionsupporting
confidence: 88%
“…In order to fully understand the impact of Epichloë infection on perennial ryegrass gene expression, we performed deep mRNA sequencing (RNAseq) on endophyte‐infected and endophyte‐free plants. This study furthers an earlier SOLiD‐SAGE analysis of E. festucae in association with red fescue grass performed by Ambrose & Belanger () that identified c . 200 host genes which are differentially expressed during a mutualistic association.…”
Section: Introductionsupporting
confidence: 88%
“…In general, endophytic fungi are similar to plant pathogenic fungi in possessing glucan hydrolase-32 (GH32 invertase) enzymes that convert sucrose into glucose and fructose for catabolism [47]. Fungal invertase activity and presence of invertase gene transcripts have been reported in some of the grass endophytes [48,49], so under the conditions imposed in our study, fungal enzymes may play at least a partial role in the observed increases in these free sugars.…”
Section: Discussionmentioning
confidence: 82%
“…High‐throughput sequencing of mRNA (RNA‐seq) is a powerful approach to evaluate transcriptional responses to biotic and abiotic changes, even without prior genomic sequence information. We (Dinkins et al ., ) and others (Johnson et al ., ; Felitti et al ., ; Khan et al ., ; Ambrose & Belanger, ; Dupont et al ., ) previously have reported a number of differentially expressed genes (DEGs) in response to the presence of Epichloë species in several grass hosts. The goal of this work was to monitor whole genome expression utilizing a genetically identical tall fescue clone harbouring E. coenophiala (E+) and without E. coenophiala (E−), to identify genes that are responsive to the endophyte status of the host.…”
Section: Introductionmentioning
confidence: 99%